Strategi Word Of Mouth Dalam Meningkatkan Jumlah Member Baru: Studi Etnografi Pada Member Alif Gym Makassar - Syam, Andi Hendra; Rais (LPPM STIE Tri Dharma Nusantara - Makassar, 2025)
Word of Mouth (WOM) strategies have become a key driver in increasing the number of new members at Alif Gym Makassar. This study uses an ethnographic approach to analyze how WOM is formed, practiced, and interpreted by the gym's member community. Data were collected through participant observation, in-depth interviews with 10 active members, and social media content analysis. The results show that WOM at Alif Gym develops through four main mechanisms: (1) personal recommendations as an emotional bridge to reduce anxiety among prospective members, (2) visual practices such as social media posts as a form of social validation, (3) the role of informal opinion leaders in disseminating healthy lifestyle innovations, and (4) WOM as a symbol of solidarity and collective identity. These findings reinforce the theories of symbolic interactionism (Blumer, 1969) and diffusion of innovation (Rogers, 2003), by demonstrating that the power of WOM lies in the authenticity of experiences and the collective socio-cultural context of the Bugis-Makassar community. This study provides practical implications for the fitness industry to optimize community-based marketing strategies and interpersonal relationships